Challenges Faced by Students When Utilizing Modal Verbs - Kurniawan, Gail Aika; Azhimia, Faida; Rahman, Faisal (Universitas Teuku Umar, 2024)
Modal auxiliaries, a grammatical category akin to auxiliary verbs, serve to convey notions of truth, prediction, or possibility. This study delves into the challenges encountered by students while grappling with modal verbs during the 2022/2023 academic year at junior high school. The primary objective is to find out the hurdles students face when employing modal verbs in their language acquisition journey. This research employed a mixed-methods focused on a sample group of 17 eighth-grade students. The research tools utilized included questionnaires and structured interviews. The data analysis encompassed three key stages: data reduction, data presentation, and data conclusion. From the comprehensive analysis of the data, it becomes evident that students encounter considerable difficulties when it comes to effectively using modal verbs. These challenges extend to comprehending the function, form, usage, and materials that facilitate modal learning. Upon careful consideration of the questionnaire responses and interview findings, it is apparent that students face notable obstacles in their utilization of modal verbs, particularly in understanding their functions, practical applications, linguistic forms, and the instructional resources necessary to enhance their grasp of this grammatical construct.